Case of renal mucinous tubular and spindle cell carcinoma with high nuclear grade. Issue 4 (11th May 2019) - Hatayama, Tomoya; Sekino, Yohei; Shikuma, Hiroyuki; Mukai, Sakurako; Muto, Masayuki; Miyamoto, Shunsuke; Sadahide, Kosuke; Fukuoka, Kenichiro; Fuji, Shinsuke; Goto, Keisuke; Shinmei, Shunsuke; Hieda, Keisuke; et al.
Abstract : Introduction: Renal mucinous tubular and spindle cell carcinoma is a rare subtype of renal cell carcinoma newly added to the World Health Organization classification in 2004. Although it has been considered as a tumor with good prognosis, aggressive cases have recently been reported. Case presentation: A 52‐year‐old man was diagnosed as having left renal cell carcinoma. Open radical left nephrectomy and left‐sided pelvic lymph nodes dissection were performed. Pathological diagnosis revealed a renal mucinous tubular and spindle cell carcinoma with high nuclear grade and extra‐regional lymph nodes metastasis classified as pT3aN0M1. After nephrectomy, metastasis at second lumbar vertebra and lymph nodes recurrence were occurred. Conclusion: This tumor with high nuclear grade may be potentially aggressive and carries a poor prognosis.